Genetic and Linkage Studies of New Autosomal Sex-Limited Mutant Hairless Antenna in Anopheles stephensi Liston. (4th January 2016) - Madhyastha, A. Dinesh; Shetty, N. J.
Abstract : A new morphological mutant hairless antenna ( hla ) was induced in the mosquito Anopheles stephensi by γ -irradiation. The expression of the mutant in the male adult revealed the antennae without the hairs. The inheritance pattern from our data demonstrates that hairless antenna is essentially sex-limited to males and is autosomal and recessive. The linkage relationships studies between the hairless antenna and greyish brown larva ( grb ) mutant indicated independent assortment and are present on different chromosomes, while the linkage relationship studies between the hairless antenna and ruby eye ( ru ) mutant revealed the suppression of hla by the ru gene in heterozygous condition. These mutants can be useful in conducting basic and applied research such as construction of linkage maps and understanding biochemical pathways and in genetic control programmes.